ANALISIS FAKTOR PENENTU DAYA TARIK PRODUK PADA PASAR UKM LOPAIT KECAMATAN TUNTANG KABUPATEN SEMARANG - Afandi, Pandi (AMONG MAKARTI, 2008)
Product Fascination which sell on the market by seller very determining of succes and exsistence of merchant UKM in vending its merchandise. The Target of this research is to know attributes that determine Product Facination by buyer at UKM of Lopait Kecamatan Tuntang Kabupaten Semarang. Result of Crosstabs multitable depict the existence of relation of line and column in 3 variable analysed by of product price, excellence of product and supporter product as determinant of product fascination. While from result test the Chi-Square to third variable determinant covering product price, product excellence and availibility of supporter product as determinant of product fascination obtained first value chi-square of 6,00 by chi-square is tables of equal to 3,8415, hence value chi-square bigger than chi-square table with by asymp is sig. 0,014 under alpha 0,05. That way also result of test chi-square secondly obtained by value chi-square equal to 15,418 and chi-square table 3,8415 so that assess the compared to bigger chi-square chi-square table with asymp sig 0,00. From both result test the the chi-square show the result which signifikan HO refused and HA accepted, so that there is related link that product price, product excellence, availibility of supporter product as determinant of product fascination which perception by " UKM of Lopait Kecamatan Tuntang Kabupaten Semarang". The importance also the improvement of service quality to all buyer, like way of speaking, way of offering goods and other friendly and sympathetic represent, one of the suggestion given from this research result. Keyword : Product Fascination, Product Price, Product Excellence, Availibility of Supporter Product